Research progress of CD80 in the development of immunotherapy drugs - Li, Lanying; Yang, Lei; Jiang, DePeng (Frontiers in Immunology, 2024)
CD80 is a molecule that plays an important role in the immune system, especially during T-cell activation, and its ligands are mainly CD28, PD-L1, and CTLA-4. CD80 is expressed on the surface of tumor cells, and it can be used as a molecular target in the process of T-cell anti-tumor immune response. In autoimmune diseases, CD80 can also regulate autoimmune diseases by modulating immunity. This review mainly focus on the role of CD80 in the immune system, as well as the research progress on the application of CD80-related immunopharmaceuticals in the treatment of tumors and autoimmune diseases.